Retinoic acid suppresses IL‐17 production and pathogenic activity of γδ T cells in CNS autoimmunity. Issue 8 (10th May 2016) - Raverdeau, Mathilde; Breen, Conor J; Misiak, Alicja; Mills, Kingston HG
Abstract : Retinoic acid (RA) in the steady state enhances induction of Foxp3 + regulatory T (Treg) cells and inhibits differentiation of Th1 and Th17 cells, thereby maintaining tolerance, but can in inflammatory conditions promote effector Th1 and Th17 cells that mediate inflammation. IL‐17‐producing γδ T cells have recently been shown to have a major pathogenic role in autoimmune diseases. Here, we examined the immunomodulatory effects of RA on γδ T cells. We found that RA had a dramatic suppressive effect on IL‐17A and IL‐17F production by γδ T cells stimulated with IL‐1β and IL‐23. RA suppressed RORγt, IL‐1R and IL‐23R expression in γδ T cells. Treatment of mice with RA suppressed IL‐17 production by γδ T cells in vivo . Furthermore, treatment of T cells with RA attenuated their ability to induce disease in experimental autoimmune encephalomyelitis (EAE), a murine model for multiple sclerosis. This was associated with a reduction in the number of central nervous system‐infiltrating γδ T cells, but also CD4 + T cells that produced IL‐17A, IL‐17F or GM‐CSF. Interestingly, treatment of γδ T cells with RA or removal of γδ T cells from a bulk population of T cells significantly reduced their capacity to induce EAE, demonstrating a critical role for γδ T cells in promoting pathogenic Th17 cells. Our findings demonstrate that the anti‐inflammatory properties of RA are mediated in part by suppressing STAT3‐mediated activation of cytokine production and cytokine receptor expression in γδ T cells, which suppresses their ability to activate Th17 cells.